(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
We investigated the perception of students in a painting workshop about the continuity of the course in the period of social isolation. Our emphasis was: in the specificities related to the new teaching-learning model, in performance of the teachers, in the scope of the interactional activities used and in the importance of the activities developed for the maintenance of the quality of life of the course participants. Data collection and analysis are based on the application of a questionnaire. Most participants prefer the face-to-face modality, which they consider more productive, although they admit the importance of maintaining the course remotely, as this contributes to well-being, mental health and learning. Our data indicate that the technology reduces distance and facilitates interaction in this moment we are living, but it does not replace physical contact.